Replacement of fish oil by alternative n-3 LC-PUFA rich lipid sources in diets for European sea bass (Dicentrarchus labrax) - Marques, Alexandra; Canada, Paula; Costa, Cátia; Basto, Ana; Piloto, Fátima; Salgado, Maria Antónia; Abreu, Helena; Dias, Jorge; Valente, Luisa M. P. (Frontiers in Marine Science, 2023)
Introduction In order to ensure lipid quality of cultured fish and an environmentally sustainable production, new alternative sources of EPA and DHA are needed to replace traditional lipid sources, such as fish oil. Methods Different combinations of alternative marine lipid sources rich in n-3 LC-PUFA available in the market were herein evaluated to replace traditional fish oil (sardine oil) in diets for European sea bass (Dicentrarchus labrax). A commercial-type diet (CTRL), containing 1.6% of EPA + DHA, 5% sardine oil and 8% rapeseed oil was used as a negative control. Another diet (SARDINE) formulated with 8.5% sardine oil, 4.5% rapeseed oil and 2.5% EPA + DHA was used as the positive control. Three experimental diets were formulated to completely replace sardine oil with alternative sources, targeting approximately the same EPA + DHA level as the positive control: the SALMON diet contained 9.9% salmon by-product oil mixed with 3.1% of an algal oil rich in EPA and DHA, while the ALGARAPE and the ALGASOY diets included 4.4% of the algal oil and 8.6% of either rapeseed or soybean oil, respectively. A sixth diet (ALGABLEND) was formulated to partially replace sardine oil with salmon by-product oil and rapeseed oil, balanced with 2% of algae biomass. The experimental diets were hand-fed to 118 g fish for 54 days. Results All diets were well-accepted by fish and no significant differences were found in feed efficiency, growth performance, somatic indexes or whole body composition among treatments. At the end of the trial, regardless the dietary EPA + DHA level, all fillets contained more than 250 mg of EPA + DHA per 100 g fresh weight, meeting EFSA recommendations for cardiovascular risk prevention for European adults (> 250 mg day -1). Discussion Overall, this study demonstrated that combining expensive sources of n-3 LC PUFA (Veramaris® or Algaessence Feed™ with low-priced sustainable oils (salmon by-products oil or vegetable oils) allows fortifying European sea bass flesh with EPA and DHA, without major textural changes. This approach is a successful strategy for mitigating the negative effects associated with the high inclusion of vegetable oils. However, the retention of n-3 LC-PUFA in muscle was not significantly increased, suggesting that there is a maximum dietary threshold beyond which β-oxidation might be promoted, and hence there is no advantage in increasing the dietary level of these fatty acids in European sea bass diets.